Preparation method and application of a PtRu-CeO2-based composite catalyst supported by an activation material
By designing the PtRu-CeO2-based composite catalyst supported by the activated material, the problems of insufficient activity and high cost of dichloromethane at low temperatures in the prior art are solved, and efficient, stable and economical catalytic degradation effect is achieved.
Patent Information
- Application Number
- CN202311695860.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-12-12
AI Technical Summary
The prior art catalysts with high activity against dichloromethane (CVOCs) at low temperatures and cost considerations are difficult to design, and the catalyst support is easily attacked by halogen, resulting in inactivation of the active site.
Using the activated material-supported PtRu-CeO2-based composite catalyst, the PtRu-CeO2-based composite catalyst is formed by compounding regenerated ruthenium chloride with CeO2 and introducing high catalytic activity at low temperatures. Ru is used to accelerate the conversion process of Cl-to-Cl2, reduce the reaction temperature, and reduce the deep chlorination of metal components and the formation of polychlorinated by-products.
It achieves high activity and selectivity for dichloromethane at low temperatures, and reduces the cost of the catalyst, avoids the attack of halogen on the active site, and improves the stability of the catalyst.
Smart Images

Figure CN117753412B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental catalysis technology, and specifically relates to a PtRu-CeO 2 The invention relates to a preparation method of a composite catalyst and its application. Background Art
[0002] With the rapid growth of global automobile demand, the treatment of waste tires and organic demolition residues has become a serious problem. Incineration is a common technology for the treatment of waste tires and organic demolition residues, but incineration is prone to produce secondary pollution such as exhaust gas and heavy metal smoke. In contrast, pyrolysis technology is considered to be a promising technology for the treatment of waste tires and organic demolition residues because of its advantages such as reducing secondary pollution and promoting the conversion of high-value products. Specifically, this technology can convert the organic matter in waste tires and organic demolition residues into storable energy mainly composed of fuel gas, fuel oil and carbon black. However, because they contain composite plastics such as modified polyvinyl chloride, waste tires and organic demolition residues are prone to release a variety of toxic chlorinated volatile organic compounds (CVOCs) during the pyrolysis process. CVOCs are O 3 One of the precursors of high concentration and persistent O 3 It is easy to form photochemical smog that is harmful to the atmosphere. In addition, CVOCs such as dichloromethane are listed as suspected carcinogens by the International Agency for Research on Cancer. Therefore, it is of great significance to study the reduction of CVOCs in the pyrolysis exhaust gas of waste tires and organic demolition residues.
[0003] In recent years, various CVOCs emission reduction technologies have been widely developed, such as adsorption, absorption, incineration, thermal catalytic oxidation, photocatalytic degradation, catalytic hydrogenation dechlorination, etc. Among these methods, thermal catalytic oxidation is considered to be one of the most promising CVOCs emission reduction technologies due to its advantages of high efficiency, environmental protection, and energy saving. Many CVOCs catalysts have been developed, especially precious metal catalysts with good catalytic activity for CVOCs at low temperatures, which have attracted much attention. However, their wide application in industry is limited by factors such as high price and easy poisoning. For example, precious metal catalysts such as Pt, Pd, Rh, and Au are easily catalyzed by Cl dissociated from CVOCs. - Attack active sites, induce electrophilic chlorination reaction and reduce activity. In order to solve this problem, a variety of products with Zeolite adsorption materials with acidic sites are used as catalyst supports to promote the adsorption of CVOCs and the breaking of C-Cl bonds, thereby improving the catalytic activity. Another effective approach is to dope CeO 2 、MnO x CrO x Transition metal oxides such as iodine can be added to improve the redox properties of the catalyst and enhance its resistance to chlorine poisoning.
[0004] However, the introduction of Zeolite materials with acidic sites are prone to the appearance of incomplete oxidation byproducts due to the lack of redox components, which affects the catalytic conversion rate; while doping with transition metal oxides is prone to produce highly active chlorine gas and form polychlorinated byproducts, reducing the catalytic activity. 2 It has high activity against CVOCs, but is easily deactivated by chlorine occupying the active sites. As an efficient catalyst for the Deacon reaction, Ru converts chlorine to Cl 2 However, at high temperatures, Cl 2 The increase in activity will lead to an increase in chlorination side reactions and polychlorinated byproducts in the system. How to design a catalyst that has high activity for CVOCs at low temperatures and takes cost into consideration is a difficult point. In addition, how to select a type of catalytic carrier that can avoid halogen attack on active sites and disperse active sites, and how to select an adsorption material with moderate acidity, high specific surface area, and good stability, or enhance resistance to chlorine as a catalyst carrier while maintaining its own structure is another difficulty. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a PtRu-CeO 2 The invention discloses a preparation method and application of a composite catalyst based on the present invention. The catalyst prepared by the method can thermally catalyze the degradation of dichloromethane and has high selectivity, catalytic activity and stability.
[0006] The present invention is a kind of PtRu-CeO supported by an activation material 2 The preparation method of the composite catalyst comprises the following steps:
[0007] Anhydrous citric acid is mixed with deionized water to obtain a citric acid solution; the prepared pre-treated regenerated ruthenium chloride solution and cerium nitrate solution are then mixed to obtain a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment;
[0008] The component of the ruthenium precipitate at the end of the high-temperature alloy waste treatment is ruthenium hydroxide;
[0009] The activated adsorbent material ASM was added to the lyogel, and ultrasonic stirring, low-temperature vacuum drying, and high-temperature calcination were performed in sequence to obtain ASM-loaded Ru-CeO 2 Catalyst, namely Ru-CeO 2 / ASM; the adsorption material includes ZS, AC, PC;
[0010] The platinum precursor H 2 PtCl 6 The solution was added dropwise to the Ru-CeO 2 / ASM catalyst surface to obtain an initial wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain ASM-supported PtRu-CeO 2 Composite catalyst, namely PtRu-CeO 2 / ASM.
[0011] In the present invention, the activated carrier has a high specific surface area and is loaded with PtRu-CeO 2 The resulting catalyst has higher activity, selectivity and good stability.
[0012] The volume ratio of anhydrous citric acid to deionized water is 1:(20-30); the concentrations of the regenerated ruthenium chloride solution and the cerium nitrate solution are both (9-10) mg / L, and are mixed at a volume ratio of 1:(15-18) to form a ruthenium-cerium mixed solution;
[0013] The ruthenium-cerium mixed solution and the citric acid solution are mixed and stirred at a volume ratio of 1:(8-9); the stirring rate is 300-500 rpm, and the time is 8-10 hours; the low-temperature concentration temperature is 85-90° C., and the concentration time is 3-5 hours;
[0014] The pretreatment method for regenerating ruthenium chloride in the present invention is to sequentially wash, acid-leach, concentrate and vacuum-dry the ruthenium precipitate at the end of the high-temperature alloy waste treatment to obtain crystalline ruthenium chloride;
[0015] The number of water washings during the pretreatment regeneration of ruthenium chloride is 2 to 3 times; the acid leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10-12 mol / L; the concentration temperature is 90-100°C, and the concentration time is 9-10h; the vacuum drying temperature is 60-80°C, and the drying time is 5-6h;
[0016] The adsorption material activation method of the present invention is to stir the calcined ZS, AC and PC in a 0.1-1 mol / L acid solution for 1-2 hours respectively, filter and wash with deionized water for 2-3 times and dry at 100-120° C. for 15-16 hours to obtain three activated adsorption materials AZS, AAC and APC; the ZS activation acid solution is a sulfuric acid solution, and the AC and PC activation acid solutions are both nitric acid solutions; the ZS calcination temperature is 500-600° C., and the calcination time is 3-4 hours;
[0017] The mass ratio of the adsorption material to the volume of the liquid gel is (15-17) mg:10 mL; the ultrasonic stirring rate is 300-500 rpm, and the time is 8-10 hours; the vacuum drying temperature is 90-95° C., and the drying time is 3-5 hours; the high-temperature calcination temperature is 390-450° C., and the time is 1-2 hours;
[0018] In the present invention, the H 2 PtCl6 The solution concentration is (9-10) mg / L; the secondary low-temperature vacuum drying temperature is 90-95°C, and the drying time is 3-5 hours; the secondary high-temperature calcination temperature is 390-450°C, and the time is 1-2 hours; the PtRu-CeO 2 The loading amount of the ternary composite catalyst relative to ASM is (0.3-0.7) wt% Pt, (0.3-0.7) wt% Ru and (18-21) wt% CeO 2 The obtained composite catalyst is labeled as (0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO 2 / AZS、(0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO 2 / AAC and (0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO 2 / APC;
[0019] In a specific embodiment, the composite catalyst is preferably N 2 Or vacuum storage.
[0020] The present invention provides a PtRu-CeO supported by an activation material 2 The application of the composite catalyst is used for the catalytic oxidation of dichloromethane, and the specific steps are as follows:
[0021] (1) Dichloromethane standard gas and O are introduced into a quartz tube reactor containing a composite catalyst. 2 The mixed gas was subjected to a catalytic oxidation reaction experiment; the heating temperature range of the quartz tube reactor was 130-390°C, the temperature point interval was 25-35°C, and each temperature point was maintained for 40-60 minutes;
[0022] (2) PtRu-CeO at 340-350℃ 2 / ASM catalyst stability test, the test time is 55-60h; bubbling air in heated deionized water to introduce water vapor into the reaction system to conduct water stability test;
[0023] The composite catalyst PtRu-CeO 2 / ASM is prepared by the preparation method described in the above technical scheme.
[0024] The present invention was carried out under two humidity conditions: dry and 5 vol.%, and the composite catalyst under dry was marked as 0.5Pt0.5Ru-20CeO 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC; the composite catalyst at 5 vol.% humidity is marked as 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC(wet);
[0025] The mass of the composite catalyst is 150-200 mg; the concentration of dichloromethane is 500-600 ppm (N 2 Balance), O 2 The content is 20-21 vol.%; the total flow rate of the reaction gas is 40-50 mL / min; the space velocity of the catalytic oxidation is 12000-15000 mL / (g·h); the catalytic degradation tail gas is detected by a gas chromatograph equipped with TCD and FID detectors; the heating temperature of the deionized water is 60-75°C; the water vapor concentration is 5-10 vol.%, and the water stability test number is 2-3 times.
[0026] The present invention uses the above-mentioned different activated adsorption materials loaded with PtRu-CeO 2 The catalyst is used for thermal catalytic degradation of dichloromethane. CeO 2 It has high activity in the catalytic degradation of dichloromethane, but the re-dissociation and Cl - The strong adsorption on the active sites makes it prone to rapid deactivation. At lower temperatures, Ru has a strong affinity for the dissociated Cl - Fast to Cl 2 The conversion has good catalytic ability, which not only inhibits the deep chlorination of metal oxides and the formation of organic polychlorinated by-products, but also reduces the Cl 2 Potential for increased polychlorinated by-products.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] The use of regenerated ruthenium chloride as one of the raw materials for preparing the composite catalyst greatly reduces the cost of the raw materials for the catalytic reaction; by introducing the Ru component and combining it with CeO 2 Compound, accelerate the Cl in the system - To Cl 2 The conversion process greatly reduces the dissociation of Cl in the reaction - CeO 2 Activity effect; by introducing Pt with high catalytic activity at low temperature, the temperature requirement of the reaction system is reduced, forming PtRu-CeO 2 The low reaction temperature greatly reduces the possibility of deep chlorination of metal components and the generation of organic polychlorinated byproducts in the system; by introducing the double noble metal PtRu and combining it with CeO2 The composite is conducive to the formation of smaller-sized dual noble metal nanoparticles, which increases the contact area with the ZS framework and promotes the redox activity of the composite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 0.5Pt0.5Ru-20CeO in Example 1 of the present invention 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC and 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC(wet) thermal catalytic dichloromethane conversion test results.
[0030] Figure 2 0.5Pt0.5Ru-20CeO in Example 1 of the present invention 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC and 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC(wet) catalytic degradation of CO 2 Yield.
[0031] Figure 3 0.5Pt0.5Ru-20CeO in Example 1 of the present invention 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC and 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC (wet) catalytic degradation products of HCl and CH 3 Selectivity of Cl.
[0032] Figure 40.5Pt0.5Ru-20CeO in Example 3 of the present invention 2 / AZS、0.3Pt0.7Ru-20CeO 2 / AZS、0.7Pt0.3Ru-20CeO 2 / AZS、Ru-20CeO 2 / AZS dichloromethane conversion test results. DETAILED DESCRIPTION
[0033] In order to further illustrate the present invention, the following is a PtRu-CeO supported by an activation material provided by the present invention in combination with an embodiment. 2 The preparation method and application of the composite catalyst are described in detail, but the embodiments of the present invention are not limited thereto. In the following description, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0034] Example 1
[0035] A PtRu-CeO supported by different activated carriers 2 Based composite catalyst, namely PtRu-CeO 2 / ASM, Pt, Ru, CeO 2 The average loading amounts are 0.5wt%, 0.5wt% and 20wt% respectively, and the synthesis method is as follows:
[0036] S1. Anhydrous citric acid and deionized water are mixed in a volume ratio of 1:20 to obtain a citric acid solution; then, equal concentrations of 9 mg / L pretreated regenerated ruthenium chloride solution and cerium nitrate solution are mixed in a volume ratio of 1:15 to form a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment; the volume ratio of the ruthenium-cerium mixed solution to the citric acid solution is 1:8; The force stirring rate is 300rpm and the time is 8h; the low-temperature concentration temperature is 85℃ and the concentration time is 3h; the preparation method of the above regenerated ruthenium chloride solution is: the ruthenium precipitate at the end of the high-temperature alloy waste treatment is sequentially washed with water, acid-leached, concentrated and vacuum-dried to obtain crystalline ruthenium chloride; the water washing times are 3 times; the acid leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10mol / L; the concentration temperature is 90℃ and the concentration time is 9h; the vacuum drying temperature is 60℃ and the drying time is 5h.
[0037] S2. Add the activated adsorbent material ASM to the liquid gel, perform ultrasonic stirring, low-temperature vacuum drying, and high-temperature calcination in sequence to obtain ASM-loaded Ru-CeO 2 Catalyst, namely Ru-CeO 2 / ASM; the adsorbent material includes ZS, AC, and PC; the activation method of the above adsorbent material is to stir the calcined ZS, AC, and PC in a 0.3 mol / L acid solution for 2 hours, filter, wash with deionized water for 3 times, and dry at 120°C for 16 hours to obtain three activated adsorbent materials AZS, AAC, and APC; the ZS activation acid solution is a sulfuric acid solution, and the AC and PC activation acid solutions are both nitric acid solutions; the calcination temperature of ZS is 600°C and the time is 4 hours; the mass of the adsorbent material and the volume ratio of the liquid gel are 15 mg:10 mL; the ultrasonic stirring rate is 500 rpm and the time is 8 hours; the vacuum drying temperature is 95°C and the drying time is 3 hours; the high-temperature calcination temperature is 390°C and the time is 1 hour.
[0038] S3. Add the platinum precursor H 2 PtCl 6 The solution was added dropwise to the Ru-CeO 2 / ASM catalyst surface to obtain an initial wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain ASM-supported PtRu-CeO 2 Composite catalyst, namely PtRu-CeO 2 / ASM. Above H 2 PtCl 6 The solution concentration is 10 mg / L; the secondary low-temperature vacuum drying temperature is 95°C and the drying time is 3 hours; the secondary high-temperature calcination temperature is 390°C and the time is 1 hour; the PtRu-CeO 2 The loading amount of the ternary composite catalyst relative to ASM is 0.5wt% Pt, 0.5wt% Ru and 20wt% CeO 2 The obtained composite catalyst is labeled as 0.5Pt0.5Ru-20CeO 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC and 0.5Pt0.5Ru-20CeO 2 / APC.
[0039] S4. In a quartz tube reactor containing 150 mg of the composite catalyst, 500 ppm (N 2 Balance) dichloromethane standard gas and content is 21vol.% 2 The catalytic oxidation reaction experiment was carried out with the mixed gas of 40 mL / min and the space velocity of the reaction gas was 12000 mL / (g·h). The quartz tube reactor was heated from 145°C to 385°C with a temperature interval of 30°C and each temperature point was maintained for 50 min. The system humidity was dry and 5 vol.%, respectively. The composite catalyst at 5 vol.% humidity was marked as 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC (wet). The catalytic degradation tail gas is detected by gas chromatography equipped with TCD and FID detectors. 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC and 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 The thermal catalytic degradation of dichloromethane was carried out using composite catalysts such as / APC(wet). The activity and selectivity test results are summarized in Figures 1 to 3 The test results show that in 0.5Pt0.5Ru-20CeO 2 / AZS、0.5Pt0.5Ru-20CeO 2 / AAC、0.5Pt0.5Ru-20CeO 2 / APC and 0.5Pt0.5Ru-20CeO 2 / AZS(wet),0.5Pt0.5Ru-20CeO 2 / AAC(wet),0.5Pt0.5Ru-20CeO 2 / APC (wet), 0.5Pt0.5Ru-20CeO 2 The activity of the AZS (wet) catalyst was the best, with a conversion rate of 97% to dichloromethane at 295°C.
[0040] Example 2
[0041] This embodiment provides a PtRu-CeO supported by an activation material. 2 The preparation method and application of the composite catalyst are the same as those in Example 1 of the present invention, except that the adsorbent material used is ZS and the concentration of the acid solution used for activation is changed. The calcined ZS is treated with a 1 mol / L acid solution to obtain the activated adsorbent material AZS. The details are as follows:
[0042] A PtRu-CeO supported by different activated carriers 2 Based composite catalyst, namely PtRu-CeO 2 / ASM, Pt, Ru, CeO 2The average loading amounts are 0.5wt%, 0.5wt% and 20wt% respectively, and the synthesis method is as follows:
[0043] S1. Anhydrous citric acid and deionized water are mixed in a volume ratio of 1:20 to obtain a citric acid solution; then, equal concentrations of 9 mg / L pretreated regenerated ruthenium chloride solution and cerium nitrate solution are mixed in a volume ratio of 1:15 to form a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment; the volume ratio of the ruthenium-cerium mixed solution to the citric acid solution is 1:8; The force stirring rate is 300rpm and the time is 8h; the low-temperature concentration temperature is 85℃ and the concentration time is 3h; the preparation method of the above regenerated ruthenium chloride solution is: the ruthenium precipitate at the end of the high-temperature alloy waste treatment is sequentially washed with water, acid-leached, concentrated and vacuum-dried to obtain crystalline ruthenium chloride; the water washing times are 3 times; the acid leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10mol / L; the concentration temperature is 90℃ and the concentration time is 9h; the vacuum drying temperature is 60℃ and the drying time is 5h.
[0044] S2. Add the activated adsorbent material AZS to the liquid gel, perform ultrasonic stirring, low-temperature vacuum drying, and high-temperature calcination in sequence to obtain AZS-loaded Ru-CeO 2 Catalyst, namely Ru-CeO 2 / AZS; the activation method of the adsorption material AZS is as follows: calcined ZS is stirred in a 1mol / L acid solution for 2h, filtered, washed with deionized water for 3 times and dried at 120°C for 16h to obtain the activated adsorption material AZS; the ZS activation acid solution is a sulfuric acid solution; the calcination temperature of ZS is 600°C and the time is 4h; the ratio of the mass of the adsorption material to the volume of the liquid gel is 15mg:10mL; the ultrasonic stirring rate is 500rpm and the time is 8h; the vacuum drying temperature is 95°C and the drying time is 3h; the high-temperature calcination temperature is 390°C and the time is 1h.
[0045] S3. Add the platinum precursor H 2 PtCl 6 The solution was added dropwise to the Ru-CeO 2 / AZS catalyst surface to obtain an initial wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain AZS-supported PtRu-CeO 2 Composite catalyst, namely PtRu-CeO 2 / AZS. Above H 2 PtCl 6 The solution concentration is 10 mg / L; the secondary low-temperature vacuum drying temperature is 95°C and the drying time is 4 hours; the secondary high-temperature calcination temperature is 390°C and the time is 1 hour; the PtRu-CeO2 The loading amount of the ternary composite catalyst relative to AZS is 0.5wt% Pt, 0.5wt% Ru and 20wt% CeO 2 The obtained composite catalyst is labeled as 0.5Pt0.5Ru-20CeO 2 / AZS.
[0046] S4. In a quartz tube reactor containing 150 mg of the composite catalyst, 500 ppm (N 2 Balance) dichloromethane standard gas and content is 21vol.% 2 The catalytic oxidation reaction experiment was carried out on the mixed gas of 1 mol / L acid treatment (the adsorbent material is marked as AZS-1) and the total flow rate of the reaction gas was 40 mL / min, and the space velocity was 12000 mL / (g·h). The quartz tube reactor was heated from 145°C to 385°C, the temperature point interval was 30°C, and each temperature point was maintained for 50 min. The system humidity was dry and 5 vol.% respectively. In this example, 0.5Pt0.5Ru-20CeO 2 / AZS composite catalyst was used for thermal catalytic dichloromethane degradation experiment. The experimental results show that compared with 0.5Pt0.5Ru-20CeO 2 / AZS, 0.5Pt0.5Ru-20CeO 2 / AZS-1 catalyst has a weaker degradation effect on dichloromethane. The experimental results at 325℃ show that 0.5Pt0.5Ru-20CeO 2 / AZS and 0.5Pt0.5Ru-20CeO 2 The conversion rates of / AZS-1 to dichloromethane were 95% and 81%, respectively. The reason may be that the activation treatment with too high acid solution concentration will destroy part of the pore structure of the adsorption carrier material AZS and reduce its porosity, resulting in a decrease in the catalytic performance of the composite catalyst to dichloromethane; on the contrary, the activation treatment with a lower acid solution concentration is conducive to improving the acid sites of the adsorption carrier AZS and increasing its specific surface area, which is conducive to improving the catalytic activity of the composite catalyst to dichloromethane.
[0047] Example 3
[0048] This embodiment provides a PtRu-CeO supported by an activation material. 2 The preparation method and application of the composite catalyst are the same as those in Example 1 of the present invention, except that the composite catalyst PtRu-CeO 2 / ASM in which ASM is AZS, and Pt, Ru, CeO 2 The average loading of the composite catalysts after the change is 0.5Pt0.5Ru-20CeO 2 / AZS、0.3Pt0.7Ru-20CeO2 / AZS、0.7Pt0.3Ru-20CeO 2 / AZS. The details are as follows:
[0049] A PtRu-CeO supported by different activated carriers 2 Based composite catalyst, namely PtRu-CeO 2 / AZS, Pt, Ru, CeO 2 The average loading amounts are 0.5wt%, 0.5wt% and 20wt% respectively, and the synthesis method is as follows:
[0050] S1. Anhydrous citric acid and deionized water are mixed in a volume ratio of 1:20 to obtain a citric acid solution; then, equal concentrations of 9 mg / L pretreated regenerated ruthenium chloride solution and cerium nitrate solution are mixed in a volume ratio of 1:15 to form a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment; the volume ratio of the ruthenium-cerium mixed solution to the citric acid solution is 1:8; The magnetic stirring rate is 300 rpm and the time is 8 hours; the low-temperature concentration temperature is 85°C and the concentration time is 3 hours; the preparation method of the above regenerated ruthenium chloride solution is: the ruthenium precipitate at the end of the high-temperature alloy waste treatment is sequentially washed with water, acid-leached, concentrated and vacuum-dried to obtain crystalline ruthenium chloride; the number of water washings is 3 times; the acid-leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10 mol / L; the concentration temperature is 90°C for 9 hours; the vacuum drying temperature is 60°C and the drying time is 5 hours.
[0051] S2. Add the activated adsorbent material AZS to the liquid gel, perform ultrasonic stirring, low-temperature vacuum drying, and high-temperature calcination in sequence to obtain AZS-loaded Ru-CeO 2 Catalyst, namely Ru-CeO 2 / AZS; the activation method of the adsorbent material AZS is to stir the calcined ZS in a 0.3 mol / L acid solution for 2 h, filter it, wash it with deionized water for 3 times and dry it at 120°C for 16 h to obtain the activated adsorbent material AZS; the ZS activation acid solution is a sulfuric acid solution; the calcination temperature of ZS is 600°C, and the time is 4 h; the ratio of the mass of the adsorbent material to the volume of the liquid gel is 15 mg:10 mL; the ultrasonic stirring rate is 500 rpm, and the time is 8 h; the vacuum drying temperature is 95°C, and the drying time is 3 h; the high-temperature calcination temperature is 390°C, and the time is 1 h.
[0052] S3. Add the platinum precursor H 2 PtCl 6 The solution was added dropwise to the Ru-CeO 2 / AZS catalyst surface to obtain an initial wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain AZS-supported PtRu-CeO 2 Composite catalyst, namely PtRu-CeO 2 / AZS. Above H 2 PtCl 6 The solution concentration is 10 mg / L; the secondary low-temperature vacuum drying temperature is 95°C and the drying time is 5 h; the secondary high-temperature calcination temperature is 390°C and the time is 1 h; the PtRu-CeO 2 The loading amount of the ternary composite catalyst relative to AZS is 0.3wt% Pt-0.7wt% Ru-20wt% CeO 2 and 0.7wt%Pt-0.3wt%Ru-20wt%CeO 2。
[0053] S4. In a quartz tube reactor containing 150 mg of the composite catalyst, 500 ppm (N 2 Balance) dichloromethane standard gas and content is 21vol.% 2 The catalytic oxidation reaction experiment was carried out with the mixed gas of 40 mL / min and the space velocity of the reaction gas was 12000 mL / (g·h). The quartz tube reactor was heated from 145°C to 385°C, the temperature point interval was 30°C, and each temperature point was maintained for 50 min. The system humidity was dry and 5 vol.%. In this example, 0.5Pt0.5Ru-20CeO 2 / AZS、0.3Pt0.7Ru-20CeO 2 / AZS、0.7Pt0.3Ru-20CeO 2 / AZS、Ru-20CeO 2 / AZS composite catalysts were used for thermal catalytic dichloromethane degradation experiments. The experimental results showed that ( Figure 4 ), 0.5Pt0.5Ru-20CeO 2 / AZS、0.3Pt0.7Ru-20CeO 2 / AZS、0.7Pt0.3Ru-20CeO 2 / AZS、Ru-20CeO 2 The temperature sequence of catalytic degradation of dichloromethane by AZS is 0.5Pt0.5Ru-20CeO 2 / AZS<0.3Pt0.7Ru-20CeO 2 / AZS<0.7Pt0.3Ru-20CeO 2 / AZS <Ru-20CeO 2 / AZS. 0.5Pt0.5Ru-20CeO 2 / AZS、0.3Pt0.7Ru-20CeO 2 / AZS、0.7Pt0.3Ru-20CeO 2 / AZS、Ru-20CeO 2 The T90 values of 0.5Pt0.5Ru-20CeO / AZS catalysts are 290℃, 322℃, 355℃, and 389℃, respectively. 2 The conversion rate of / AZS to dichloromethane was 92%.
[0054] Example 4
[0055] This embodiment provides a PtRu-CeO supported by an activation material. 2 The preparation method and application of the composite catalyst are the same as those in Example 1 of the present invention, except that 0.5Pt0.5Ru-20CeO 2 / AZS catalyst stability test, the test time is 55h; bubbling air in deionized water at a temperature of 60℃ to introduce 5vol.% humidity water vapor into the reaction system, and the water stability test is carried out 3 times. The specific steps are as follows:
[0056] S1. Anhydrous citric acid and deionized water are mixed in a volume ratio of 1:20 to obtain a citric acid solution; then, equal concentrations of 9 mg / L pretreated regenerated ruthenium chloride solution and cerium nitrate solution are mixed in a volume ratio of 1:15 to form a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment; the volume ratio of the ruthenium-cerium mixed solution to the citric acid solution is 1:8; The magnetic stirring rate is 300 rpm and the time is 8 hours; the low-temperature concentration temperature is 85°C and the concentration time is 3 hours; the preparation method of the above regenerated ruthenium chloride solution is: the ruthenium precipitate at the end of the high-temperature alloy waste treatment is sequentially washed with water, acid-leached, concentrated and vacuum-dried to obtain crystalline ruthenium chloride; the number of water washings is 3 times; the acid-leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10 mol / L; the concentration temperature is 90°C for 9 hours; the vacuum drying temperature is 60°C and the drying time is 5 hours.
[0057] S2. Add the activated adsorbent material AZS to the liquid gel, perform ultrasonic stirring, low-temperature vacuum drying, and high-temperature calcination in sequence to obtain AZS-loaded Ru-CeO 2 Catalyst, namely Ru-CeO 2 / AZS; the adsorption material activation method is to stir the calcined ZS in a 0.3 mol / L acid solution for 2 h, filter it, wash it with deionized water for 3 times and dry it at 120°C for 16 h to obtain the activated adsorption material AZS; the ZS activation acid solution is a sulfuric acid solution; the calcination temperature of ZS is 600°C, and the time is 4 h; the ratio of the adsorption material mass to the liquid gel volume is 15 mg:10 mL; the ultrasonic stirring rate is 500 rpm, and the time is 8 h; the vacuum drying temperature is 95°C, and the drying time is 3 h; the high-temperature calcination temperature is 390°C, and the time is 1 h.
[0058] S3. Add the platinum precursor H 2 PtCl 6 The solution was added dropwise to the Ru-CeO 2 / AZS catalyst surface to obtain an initial wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain AZS-supported PtRu-CeO 2 Composite catalyst, namely PtRu-CeO 2 / AZS. Above H 2 PtCl 6 The solution concentration is 10 mg / L; the secondary low-temperature vacuum drying temperature is 95°C and the drying time is 3 hours; the secondary high-temperature calcination temperature is 390°C and the time is 1 hour; the PtRu-CeO 2 The loading amount of the ternary composite catalyst relative to AZS is 0.5wt% Pt, 0.5wt% Ru and 20wt% CeO 2 The obtained composite catalyst is labeled as 0.5Pt0.5Ru-20CeO 2 / AZS.
[0059] S4. In a quartz tube reactor containing 150 mg of the composite catalyst, 500 ppm (N 2 Balance) dichloromethane standard gas and content is 21vol.% 2 The catalytic oxidation reaction experiment was carried out with the mixed gas of 40 mL / min and the space velocity of the reaction gas was 12000 mL / (g·h). The quartz tube reactor was heated from 145°C to 385°C with a temperature interval of 30°C and each temperature point was maintained for 50 min. The system humidity was dry and 5 vol.%. The 0.5Pt0.5Ru-20CeO 2 / AZS catalyst stability test, the test time is 55h; bubbling air in deionized water at a temperature of 60℃ to introduce 5vol.% humidity water vapor into the reaction system, and the water stability test is carried out 3 times. 2 / AZS composite catalyst was tested for water stability. The experimental results showed that the T90 value of the second cycle was 0.5Pt0.5Ru-20CeO 2 / AZS increased the T90 value by 20℃ compared with the first cycle and remained stable in the third cycle. The results of water stability test showed that 0.5Pt0.5Ru-20CeO 2 / AZS catalyst has good catalytic stability.
[0060] The above description is only a preferred embodiment of the present invention. It should be pointed out that the present invention is not limited to the above embodiments. The above embodiments and the specification only describe the principles of the present invention. The present invention may have various changes and improvements without departing from the principle and scope of the present invention. These changes and improvements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a PtRu-CeO2-based composite catalyst supported by an activation material, characterized in that: The following steps are involved: The ruthenium-cerium liquid gel is prepared by a citric acid gel method: anhydrous citric acid is mixed with deionized water to obtain a citric acid solution; the prepared pre-treated regenerated ruthenium chloride solution and cerium nitrate solution are then mixed to obtain a ruthenium-cerium mixed solution, and then the citric acid solution is added dropwise and magnetic stirring and low-temperature concentration are performed in sequence to obtain a ruthenium-cerium liquid gel; the source of the regenerated ruthenium chloride is the ruthenium precipitate at the end of the high-temperature alloy waste treatment; The volume ratio of anhydrous citric acid to deionized water is 1:(20-30); the concentrations of the regenerated ruthenium chloride solution and the cerium nitrate solution are both (9-10) mg / L, and the ruthenium-cerium mixed solution is formed after being mixed at a volume ratio of 1:(15-18); the volume ratio of the ruthenium-cerium mixed solution to the citric acid solution is 1:(8-9); the magnetic stirring rate is 300-500 rpm, and the time is 8-10 hours; the low-temperature concentration temperature is 85-90°C, and the concentration time is 3-5 hours; Adsorption-calcination method is adopted to prepare Ru-CeO2 / ASM: activated adsorption material ASM is added into ruthenium cerium liquid gel, ultrasonic stirring, low temperature vacuum drying and high temperature calcination are carried out in sequence to obtain ASM-loaded Ru-CeO2 catalyst, namely Ru-CeO2 / ASM; the adsorption material comprises ZS: HZSM-5, AC: activated carbon, PC: porous ceramic powder; The composite catalyst PtRu-CeO2 / ASM is prepared by primary wet impregnation-secondary calcination: a platinum precursor H2PtCl6 solution is added dropwise to the surface of the Ru-CeO2 / ASM catalyst to obtain a primary wet impregnation solid; the solid is then subjected to secondary low-temperature vacuum drying and secondary high-temperature calcination to obtain an ASM-loaded PtRu-CeO2 composite catalyst, namely PtRu-CeO2 / ASM; The secondary low-temperature vacuum drying temperature is 90-95°C, and the drying time is 3-5 hours; the secondary high-temperature calcination temperature is 390-450°C, and the time is 1-2 hours.
2. The preparation method according to claim 1, characterized in that: The pretreatment method for regenerated ruthenium chloride is as follows: washing, acid leaching, concentrating and vacuum drying the ruthenium precipitate at the end of the high-temperature alloy waste treatment in sequence to obtain crystalline ruthenium chloride; the water washing times are 2 to 3 times; the acid leaching reagent is hydrochloric acid, and the concentration of the hydrochloric acid solution is 10-12 mol / L; the concentration temperature is 90-100° C., and the concentration time is 9-10 hours; the vacuum drying temperature is 60-80° C., and the drying time is 5-6 hours.
3. The preparation method according to claim 1, characterized in that: The adsorption material activation method comprises the following steps: stirring calcined ZS, AC and PC in a 0.1-1 mol / L acid solution for 1-2 hours respectively, filtering, washing with deionized water for 2-3 times and drying at 100-120° C. for 15-16 hours to obtain three activated adsorption materials AZS, AAC and APC; the ZS activation acid solution is a sulfuric acid solution, and the AC and PC activation acid solutions are both nitric acid solutions; the ZS calcination temperature is 500-600° C. and the time is 3-4 hours; the adsorption material mass and the ruthenium cerium liquid gel volume ratio is (15-17) mg:10 mL; the ultrasonic stirring rate is 300-500 rpm and the time is 8-10 hours; the low-temperature vacuum drying temperature is 90-95° C. and the drying time is 3-5 hours; the high-temperature calcination temperature is 390-450° C. and the calcination time is 1-2 hours.
4. The preparation method according to claim 1, characterized in that: The concentration of the H2PtCl6 solution is (9~10) mg / L.
5. The preparation method according to claim 1, characterized in that: The loading amount of the PtRu-CeO2 composite catalyst relative to ASM is (0.3-0.7)wt% Pt, (0.3-0.7)wt% Ru and (18-21)wt% CeO2, and the obtained composite catalysts are marked as (0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO2 / AZS, (0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO2 / AAC and (0.3-0.7)Pt(0.3-0.7)Ru-(18-21)CeO2 / APC.
6. A composite catalyst prepared according to the method described in any one of claims 1 to 5.
7. Use of the composite catalyst as claimed in claim 6, characterized in that: The method is used for catalytic oxidation of dichloromethane, comprising the following steps: (1) A catalytic oxidation reaction experiment was conducted by introducing a mixture of dichloromethane standard gas and O2 into a quartz tube reactor containing a composite catalyst; the heating temperature range of the quartz tube reactor was 130-390°C, the temperature point interval was 25-35°C, and each temperature point was maintained for 40-60 minutes; the system humidity was controlled to be less than or equal to 5 vol.%; (2) The stability test of the PtRu-CeO2 / ASM catalyst was conducted at 340-350°C for 55-60 hours; air was bubbled into the heated deionized water to introduce water vapor into the reaction system to conduct a water stability test.
8. The use according to claim 7, characterized in that: The dichloromethane concentration is 500-600ppm N2 balance, and the O2 content is 20-21vol.%; the total flow rate of the reaction gas is 40-50mL / min; and the space velocity of the catalytic oxidation is 12000-15000 mL / (gh).
9. The use according to claim 7, characterized in that: The heating temperature of the deionized water is 60-75° C.; the water vapor concentration is 5-10 vol.%, and the water stability test times are 2-3 times.
Citation Information
Patent Citations
Method for eliminating chloro aromatic hydrocarbon through low-temperature catalytic combustion
CN103962134A
Cerium-based catalyst for efficiently degrading CVOCs
CN115400745A